Determination of molybdenum in biological samples by flame atomic spectrometry after preconcentration on activated carbon - Yigmatepe, Ergul; Yaman, Mehmet (Springer Wien, 2011)
Molybdenum is well known for its toxic effects, although it is also essential for N-2-fixing cyanobacteria and several enzymes. This study proposes a simple and accurate procedure for separation, preconcentration, and determination of trace amounts of molybdenum in biological samples by flame atomic absorption spectrometry. It is based on complexation of Mo by cupferron and sorption onto activated carbon. Effects of parameters such as pH, stirring time, and amounts of activated carbon and cupferron on recovery were examined. The results demonstrated that Mo at pH range of 2.5-3.5 was quantitatively sorbed onto activated carbon as its cupferron complex. The optimum stirring time was found to be 30 min. The relative standard deviation was found to be 12% for 200 cm(3) 50 ng/cm(3) Mo using 10 replicate preconcentration procedures. The limits of detection and quantification were found to be 1.0 and 3 ng/cm(3), respectively, by preconcentration of 200 cm(3) initial sample to 2 cm(3) final volume. As a result, an enrichment factor of 100-fold was achieved. The proposed preconcentration procedure was applied to determine Mo in biological samples such as vegetables, milk, and animal liver. The molybdenum concentrations were found (as mu g/dm(3) or mu g/kg) in the range of 70-5,500 for plants, 3-124 for milk and milk powder, and 960 for liver samples.
Keywords: Spectroscopy; Metals; Ligands; Solid-phase extraction; Metal complexes